La economía y el discurso económico en la construcción de ligitimidad política en Argentina - Moench, Eric (Nómadas. Critical Journal of Social and Juridical Science, 2011)
Political legitimacy let exercise authority in democratic countries. Such legitimacy can stem from various sources. This paper is about economic practices and discourses of the first government after the 2001 crisis in Argentina. It has managed to rebuild some political authority, after a couple of years of lack of it. We are interested in search the economic as founding of legitimacy, like in less developed countries such as Argentina, the recurrent crises of economic models carry at the incoming government to base its legitimacy on the antagonism over the previous model. In this sense we want to explore which specifics forms take this process, and the limits of this practice.